2016
DOI: 10.3390/ijerph13100967
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectromagnetics Research within an Australian Context: The Australian Centre for Electromagnetic Bioeffects Research (ACEBR)

Abstract: Mobile phone subscriptions continue to increase across the world, with the electromagnetic fields (EMF) emitted by these devices, as well as by related technologies such as Wi-Fi and smart meters, now ubiquitous. This increase in use and consequent exposure to mobile communication (MC)-related EMF has led to concern about possible health effects that could arise from this exposure. Although much research has been conducted since the introduction of these technologies, uncertainty about the impact on health rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, in most cases, such as in laboratories and offices where only low current devices are used, the declaration of conformity with the CE marking is sufficient. Of course, this principle is not applied in the case of HV equipment [10]. The EMF Directive stipulates "exposure limits values" (ELV, corresponding to the internal quantity, equivalent to ICNIRP's "basic restriction") and "action levels" (the external imposed field, equivalent to ICNIRP's "reference level").…”
Section: Limits Regulations and Methods For The Emf (Electromagnetimentioning
confidence: 99%
“…However, in most cases, such as in laboratories and offices where only low current devices are used, the declaration of conformity with the CE marking is sufficient. Of course, this principle is not applied in the case of HV equipment [10]. The EMF Directive stipulates "exposure limits values" (ELV, corresponding to the internal quantity, equivalent to ICNIRP's "basic restriction") and "action levels" (the external imposed field, equivalent to ICNIRP's "reference level").…”
Section: Limits Regulations and Methods For The Emf (Electromagnetimentioning
confidence: 99%
“…We have been contributing to research in this area through our previous modelling of insulin exposure to various electric fields [52][53][54][55] and more recently, through our involvement into the Australian Center of Electromagnetic Bioeffects Research (ACEBR). [56] High-level fields of specific frequency can excite certain vibrational modes of proteins and other biomolecules, causing structural changes that can lead to misfolding and ultimately, aggregation of proteins into insoluble amyloid fibrils. [52][53][54]57,58] On the other hand, experimental studies have suggested that EMFs may be used as a therapeutic tool for the breakdown of fibrils implicated in Alzheimer's disease.…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…All-atom computer model of an amyloid peptide in solution under the influence of varying strength electromagnetic fields (EMF). [48,56] (a) ApoC-II peptide adopting an elongated conformation due to the peptide dipole alignment along the electric field direction at fields higher than 0.04 V nm À1 . (b) ApoC-II peptide adopts native-like conformation while exposed to fields , 0.04 V nm À1 in strength.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there are no prima facie reasons to expect more damage from RF-EMF than from infrared radiation, which is ubiquitous and harmless up to the thermal damage. As mentioned above, the only proven interaction mechanism within the frequencies and magnitudes relevant to mobile telecommunications is a thermal effect [2,3,44]. On the contrary to ionizing radiation, humans are protected from hyperthermia by the thermoreception.…”
Section: Mobile Phones: Carcinogenic and Other Potential Risksmentioning
confidence: 99%